DETERMINANTS OF MILLENNIALS AND GENERATION Z IN ADOPTING FAMILY TAKAFUL (Isagoge - Journal of Humanities and Social Sciences, 2025)
This study aims to analyze the factors influencing Millennials' and Generation Z’s intention to adopt family Takaful in Indonesia. Using a purposive sampling technique, data were collected through a questionnaire covering attitudes, subjective norms, behavioral control, religiosity, and digitalization. A total of 256 responses were analyzed using structural equation modeling (SEM) with a partial least squares (PLS) approach to test the proposed hypotheses. The results indicated that attitude, perceived behavioral control, religiosity, and digitalization positively and significantly influenced the intention to adopt family Takaful. However, subjective norms showed no significant effect. Attitude and digitalization emerged as the most dominant factors. Moreover, the influence of religiosity on adoption intention is stronger among women than men, while attitude is the most influential factor overall. The findings of this study suggest that increasing awareness and understanding of family Takaful among Millennials and Generation Z is crucial. Therefore, a robust and continuous literacy and education program should be implemented. The family Takaful industry must undergo a digital transformation to effectively cater to Millennials and Generation Z, and religious approaches can be leveraged to attract female customers. This study identifies the key drivers of Millennials' and Generation Z's adoption of family Takaful, highlighting the dominant roles of attitude and digitalization. This study provides valuable insights for industry stakeholders to strategically target these segments and enhance adoption rates through education and digital innovation.
Keywords: Digitalization; Family takaful; Generation z; Millennials; Religiosity